2024
DOI: 10.1021/acs.iecr.3c04540
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Potential Losses and pH Distribution in the Electrochemical Nitrate Reduction Reaction to Ammonia

Maryam Ahmadi,
Mohammadreza Nazemi

Abstract: Electrochemical nitrate reduction reaction (NO 3− RR) to ammonia is a promising route to eliminate one of the major pollutants in surface water and groundwater. When powered by renewable electricity, electrolysis provides a sustainable method to generate ammonia from nitrate ions, facilitating the transition from a linear to a circular economy. Optimizing the physical and chemical properties of electrolysis cells is crucial to making this process economically viable for widespread implementation. Here, we expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Common buffering anions, such as CO 3 2– , HCO 3 – , and PO 4 3– , alter the local pH and steer the selectivity of eNO 3 RR. , In situ pH measurements revealed that the interfacial pH near the cathode followed the trend of basic buffer > neutral buffer > acidic buffer during reaction . NH 3 production was favored in the buffered systems, with NH 3 selectivity/NO 2 – selectivity in the order acidic buffer > neutral buffer > basic buffer > non-buffered .…”
Section: Influence Of Atomic Hydrogen Production and Water Dissociationmentioning
confidence: 97%
“…Common buffering anions, such as CO 3 2– , HCO 3 – , and PO 4 3– , alter the local pH and steer the selectivity of eNO 3 RR. , In situ pH measurements revealed that the interfacial pH near the cathode followed the trend of basic buffer > neutral buffer > acidic buffer during reaction . NH 3 production was favored in the buffered systems, with NH 3 selectivity/NO 2 – selectivity in the order acidic buffer > neutral buffer > basic buffer > non-buffered .…”
Section: Influence Of Atomic Hydrogen Production and Water Dissociationmentioning
confidence: 97%